Impact of impairment loss on profitability and capital structure of listed manufacturing companies in sri lanka. - Sooriyakumaran, L.; Velnampy, T. (My University, 2014)
This paper investigates the effects of impairment of assets on profitability and capital structure of listed manufacturing companies in CSE in Sri Lanka. The study data have been collected from the financial statements during a five years periods of 2008-2012.The study attempt to find the answer to the question that does impairment of assets affect the profitability and capital structure of the companies?. The study sample consists of 37 companies. Impairment loss is independent variable and profitability and capital structure are dependent variables. The descriptive statistics were used and then Pearson's correlation coefficient was used to identify the relationship between the variables. The regression analysis was used to identify the impact of impairment loss on profitability and capital structure. The study found that impairment of assets was found to have a negative impact on profitability and capital structure. The findings also confirmed that changes by impairment have significant impact on profitability and capital structure in case of listed manufacturing companies in CSE.
Keywords: Impairment of assets; Profitability; Capital structure